Therapeutic Role and Potential Mechanism of Resveratrol in Atherosclerosis: TLR4/NF-κB/HIF-1α - Lin Guo; Xiaolu Zhang; Nuan Lv; Luming Wang; Jiali Gan; Xijuan Jiang; Yijing Wang (Hindawi Limited, 2023)
Atherosclerosis, the main pathological basis of cardiovascular disease, is a chronic inflammatory disease that severely affects the quality of human life. Resveratrol (Res) is a natural polyphenol that is a major component of many herbs and foods. The present study analyzed resveratrol from the perspective of visualization and bibliometric analysis and found that resveratrol is closely related to the inflammatory response in cardiovascular diseases (associated with atherosclerosis). To explore the specific molecular mechanism of resveratrol, network pharmacology and Kyoto Encyclopedia of Genes and Genomes (KEGG) were used, in which HIF-1α signaling may be a key pathway in the treatment of AS. Furthermore, we induced the polarization of macrophage RAW264.7 to M1 type to generate inflammatory response by the combination of lipopolysaccharide (LPS) (200 ng/mL) + interferon-γ (IFN-γ) (2.5 ng/mL). LPS and IFN-γ increased the inflammatory factor levels of IL-1β, TNF-α, and IL-6 in RAW264.7, and the proportion of M1-type macrophages also increased, but the expression of inflammatory factors decreased after resveratrol administration, which confirmed the anti-inflammatory effect of resveratrol in AS. In addition, we found that resveratrol downregulated the protein expression of toll-like receptor 4 (TLR4)/NF-κB/hypoxia inducible factor-1 alpha (HIF-1α). In conclusion, resveratrol has a significant anti-inflammatory effect, alleviates HIF-1α-mediated angiogenesis, and prevents the progression of AS through the TLR4/NF-κB signaling pathway.